Christianity, Islam, and Orisa-Religion : Three Traditions in Comparison and Interaction - Peel, J. D. Y. (John David Yeadon), 1941-2015 (Book collections on Project MUSE., 2016)
"The Yoruba of southwestern Nigeria are exceptional for the copresence among them of three religious traditions: Islam, Christianity, and the indigenous orisa-religion. In this strongly comparative study, at once historical and anthropological, Peel explores the intertwined character of the three religions and the dense imbrication of religion in all other aspects of Yoruba history up to the present. For over 400 years, the Yoruba have straddled two geocultural spheres: one reaching north over the Sahara to the world of Islam, the other linking them to the Euro-American world via the Atlantic. These two external spheres were the source of contrasting cultural influences, notably those emanating from the world religions. Moreover, the Yoruba not only imported Islam and Christianity; they exported their own orisa-religion to the New World. Before the voluntary modern diaspora that has brought many Yoruba to Euro-America, tens of thousands had been sold as slaves to the New World, bringing with them the worship of the orisa. Along the way, Peel not only offers deep insight into such important contemporary themes as religious conversion, new religious movements, relations between world religions, the conditions of religious violence, the transnational flows of contemporary religion, and the interplay between tradition and the demands of an ever-changing present but also makes a major theoretical contribution to the anthropology of world religions."--Provided by publisher